Chemical Composition and Antibacterial Activity of the Carvacrol-rich Essential Oils of Zataria multiflora Boiss. (Lamiaceae) from Southern Natural Habitats of Iran. Issue 4 (3rd July 2020) - Pourhosseini, Seyyed Hossein; Ahadi, Hamid; Aliahmadi, Atousa; Mirjalili, Mohammad Hossein
Abstract: The study of phytochemical variability and biological activity followed by selection are the main steps in the domestication and breeding of medicinal and aromatic plants. Zataria multiflora Boiss. is an aromatic perennial plant belonging to the Lamiaceae family which is native to south-western Asia. In this study, chemical variability and antibacterial activity of the essential oils (EOs) of the seven Zataria multiflora populations from southern natural habitats of Iran (Hormozgan Province) were studied for the first time separately. Hydro- distilled EOs from the aerial parts of Z. multiflora populations were analyzed by GC-FID and GC-MS. EOs content (% w/w) varied from 3.5 to 6.6 % in the studied populations. In total, eighteen compounds, representing 99.0-99.9 % of the oils were identified. Carvacrol (28.3-95.2 %), thymol (0.1-53.5 %), γ-terpinene (2.1-19.2 %) and p-cymene (1.0-6.8 %) were the major constituents of all samples. Cluster analysis of the EOs compounds clustered Z. multiflora populations into the three main chemotypes. The antibacterial activity of the EOs was investigated on Gram-positive ( Staphylococcus aureus ATCC 25923) and Gram-negative ( Escherichia coli ATCC 25922) bacteria. The results showed that the studied EOs could inhibit both food-borne pathogens, with MIC values of 0.031-1 mg/ml. These findings in comparison to previous studies indicated that Z. multiflora populations from the south of Iran are characterized by carvacrol-rich EOs which can be considered for further domestication, conservation, breeding and exploitation programs.